THE IMPORTANCE OF BIOLOGICAL RHYTHMS IN THE CONSTRUCTION OF THE DAILY ROUTINE - Светлана Альбертовна Дракина; Нина Константиновна Перевощикова (The Publishing House Medicine and Enlightenment, 2021)
The most important tasks of the state policy of the Russian Federation are the preservation and strengthening of children's health. The deterioration of the health status of children is largely due to the shift in emphasis from the health care system to the treatment of patients. The main task of pediatrics today is to restore the preventive focus of work. Of particular concern are children who begin to attend preschool institutions and schools, since this period is characterized by a high risk of realizing a hereditary predisposition to the development of diseases. At the heart of the implementation of chronic diseases in children, the leading role is given to recurrent respiratory infections. To prevent functional disorders at the level of their implementation into pathological conditions, prenosological diagnosis of many diseases, it may be useful to study the characteristics of biological rhythms in childhood.